Main goals and research outcomes of the EU Projects ELSMOR, McSAFER, and EASI-SMR: regulatory, experimental and analytical safety-related investigations - Tulkki Ville; Sanchez-Espinoza Victor Hugo; Sobecki Nicolas (EPJ Nuclear Sciences & Technologies)
Small modular reactors are being developed globally with first new builds being planned within a decade. The most near-term designs are based on light water reactor technologies. While the fundamental technology is well known, the designs aim to utilize passive safety functions and simplifies systems to drive down costs. The correct operation of these functions must be ensured for these new nuclear reactors to be licensed in Europe. This paper discusses three projects funded by Euratom Research and Training programme: ELSMOR, McSAFER, and EASI-SMR. In this paper, the main goals and selected outcomes of two European research projects that finished some months ago will be presented and discussed. In addition, the main goals and the research program of the EASI-SMR project will be described.